Performance Reviewed From Competence Integrity Training and Organizational Culture Study At Cangkringan Police Sub-District, Yogyakarta - Indro Ariyanto Saputro; Sarsono Sarsono; Supawi Pawenang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the influence of training, integrity, competence, and organizational culture on the performance of police personnel at Polsek Cangkringan, both partially (each variable individually) and simultaneously (collectively). The research is conducted by considering the importance of improving police performance as an institution responsible for public service, protection, and law enforcement at the local level. This study employs a quantitative research design with a survey approach. The population consists of all police personnel at Polsek Cangkringan, totaling 37 individuals. The sampling technique used is saturated sampling (census). Data were collected through the distribution of questionnaires. The data analysis techniques include statistical analysis using multiple linear regression, F-test, t-test, and coefficient of determination. The results indicate that training, integrity, competence, and organizational culture each have a positive effect on performance, with competence emerging as the most dominant factor. Simultaneously, these four variables have a significant effect on personnel performance, indicating that performance improvement is influenced by various internal factors within the organization.